Phytoaccumulation of chromium by hemp and ryegrass in rice husk biochars, nano-zero valent zinc and vermicompost amended tannery wastewater soil - Zulfqar, Amna; Niazi, Nabeel Khan; Saqib, Zulfiqar Ahmad; Shahid, Muhammad; Hussain, Khalid; He, Zhenli (Frontiers in Environmental Science, 2025)
Chromium (Cr) contamination of soil threatens environmental and human health, necessitating effective and sustainable remediation solutions. Here we explored the impact of rice husk biochar (RH-BC), nano-RH-BC, vermicompost, nano-zero valent zinc (nZVZn), and manganese-modified RH-BC (MnO/RH-BC) on phytoaccumulation of Cr by industrial hemp (Cannabis sativa L.) and ryegrass (Lolium perenne L.) grown in tannery wastewater-impacted Cr-contaminated soil in a pot trial. Results revealed that maximum shoot Cr concentration was observed in ryegrass with nZVZn mainly in first cutting (45 mg kg-1 DW) followed by vermicompost (42 mg kg-1 DW) > RH-BC (40 mg kg-1 DW) > nano-RH-BC (35 mg kg-1 DW) ∼ MnO/H-BC (34 mg kg-1 DW). In the case of hemp, nZVZn led to maximum shoot Cr concentration (42 mg kg-1 DW) and minimum with RH-BC (4 mg kg-1 DW); notably, hemp survived only for the first harvest. The SPAD value (chlorophyll content) was the highest with MnO/RH-BC for ryegrass and RH-BC for hemp (40 and 51, respectively) and minimum with nZVZn. Results showed that the RH-BC enhanced shoot dry weight of hemp by 664% compared to control, and MnO/RH-BC increased for ryegrass by 400%, 93%, 55%, and 21% at first, second, third, and fourth harvests, respectively. Overall, RH-BC and MnO/RH-BC-amended soils improved plant tolerance against Cr, highlighting their potential for phytoremediation of Cr-contaminated soil. Based on the findings, it is evident that Cr phytoaccumulation is a complex process and varies with plant species and amendment type, which are key factors to consider in future field trials on tannery wastewater-impacted Cr-contaminated soils.